2019
DOI: 10.5829/ije.2019.32.04a.19
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Hydrodynamic Performance of the Stepped Planing Craft and Its Step Height Effect

Abstract: A B S T R A C TOne of the most efficient methods of reducing drag on planing craft is the use of transverse step on the bottom of a hull. Applying steps on the hull reduces the contact area with water and as a result, it reduces drag of the craft. Planing craft are able to have one or two transverse steps. In this paper, numerical hydrodynamic performance of the stepped planing craft and its step height effect is investigated by making use of finite volume method (FVM). The Reynolds-Averaged Navier-Stokes (RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The average discrepancy between experimental data and numerical analysis drag, dynamic trim, and heave was less than 9%, 4%, 10.5%, as explained in Figure 7; similar validation results between numerical and experimental methods. Studies also occurred in a study carried out by Nourghassemi [22]. He stated that such discrepancy is acceptable and that the presented model can predict the hydrodynamic performance of planing craft.…”
Section: Figure 6 Grid Sizementioning
confidence: 89%
“…The average discrepancy between experimental data and numerical analysis drag, dynamic trim, and heave was less than 9%, 4%, 10.5%, as explained in Figure 7; similar validation results between numerical and experimental methods. Studies also occurred in a study carried out by Nourghassemi [22]. He stated that such discrepancy is acceptable and that the presented model can predict the hydrodynamic performance of planing craft.…”
Section: Figure 6 Grid Sizementioning
confidence: 89%
“…Hydrodynamic analysis with numerical calculations using two transverse step with different heights invented using ANSYS CFD with the k epsilon model. The study found that the ship can reduce drag and pressure distribution and created moderate performance [9].…”
Section: Introductionmentioning
confidence: 94%